Associations Between Change in Outside Time Pre- and Post-COVID-19 Public Health Restrictions and Mental Health: Brief Research Report - Cindrich, Sydney L.; Lansing, Jeni E.; Brower, Cassandra S.; McDowell, Cillian P.; Herring, Matthew P.; Meyer, Jacob D. (Frontiers in Public Health, 2021)
The novel coronavirus disease 2019 (COVID-19) and associated pandemic has resulted in systemic changes to much of life, affecting both physical and mental health. Time spent outside is associated with positive mental health; however, opportunities to be outside were likely affected by the COVID-19 public health restrictions that encouraged people not to leave their homes unless it was required. This study investigated the impact of acute COVID-19 public health restrictions on outside time in April 2020, and quantified the association between outside time and both stress and positive mental health, using secondary analyses of cross-sectional data from the COVID and Wellbeing Study. Participants (n=3,291) reported demographics, health behaviors, amount of time they spent outside pre/post COVID-19 public health restrictions (categorized as increased, maintained, or decreased), current stress (Perceived Stress Scale-4), and positive mental health (Short Warwick-Edinburgh Mental Wellbeing Scale). Outside time was lower following COVID-19 restrictions (p<0.001; Cohen’s d=-0.19). Participants who increased or maintained outside time following COVID-19 restrictions reported lower stress (p < 0.001, 5.93[5.74-6.12], Hedges’ g = -0.18; p < 0.001, mean=5.85[5.67-6.02], Hedges’ g= -0.21; respectively) and higher positive mental health (p < 0.001, 24.49[24.20-24.77], Hedges’ g= 0.21; p < 0.001, 24.78[24.52-25.03], Hedges’ g= 0.28) compared to those who decreased outside time. These findings indicate that there are likely to be negative stress and mental health implications if strategies are not implemented to encourage and maintain safe time outside during large-scale workplace and societal changes (e.g. during a pandemic).